Audit of Frequency and causes of 30-day readmission after head and neck surgery at Aga Khan Hospital Karachi: A Retrospective cross-sectional study - Muhammad Hassan Danish; Abdul Basit Shah Vardag; Huzaifa Moiz; Muhammad Wasif; Hamdan Ahmed Pasha; Mohammad Sohail Awan (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the frequency and causes of unplanned readmissions and emergency department visits of patients having undergone head and neck surgeries within 30 days of the initial surgery. Method: The cross-sectional, retrospective study was conducted at the Department of Otolaryngology and Head and Neck Surgery, Aga Khan University Hospital, Karachi, from January 2020 to June 2020 and comprised data from January 2017 to December 2019 of all patients who underwent head and neck surgery. Data was collected using a customised proforma and was analysed using SPSS 23. Results: Against 1,094 admissions, there were 142(12.97%) readmissions. Of them, 7(4.9%) were excluded due to missing data. Among the remaining 135(95.1%) subjects, 86(64%) were male and 49(36%) were females. The overall mean age was 51.1± 15.634 years. Most of the patients 82(61%) were admitted to the emergency department, Oral carcinoma was the most common primary diagnosis 89(66%), and 82(61%) of the readmitted patients were admitted through ED. There were 28(21%) patients readmitted with haemorrhage, while 63(47%) required nonsurgical treatment on readmission. Conclusion: Total rate of unplanned readmission in head and neck surgeries within 30 days was 12.97%, with bleeding and infection being the most common causes of readmission. Key Words: Patient readmissions, 30-day readmissions, Head and neck cancer, Head and neck surgery, Postoperative readmission.